Sustainable Growth Rate Analysis: Study on Companies From North-West of Romania Before and During the Pandemic - Ioana-Cristina CRACIUN (TIMOFEI); Claudia Diana SABAU-POPA (Communications of International Proceedings, 2021)
Companies to survive in a competitive world require sustainable growth. The purpose of this research is to determine if there is an influence between performance and sustainable growth of companies and to examine whether there is a positive or negative relationship between variables and sustainable growth adapted to the particularities of the real estate and constructions sector. The sustainable growth at the company level is analysed before and during the pandemic, being thus influenced by external factors. In this paper is used both qualitative and quantitative research methods. Among the qualitative research methods used it can be mentioned: observation, comparison and analysis of data. In order to achieve the main objective of the paper, the econometric analysis is based on a descriptive method and multiple regression analysis, in which the independent variables are measurements of financial performance such as financial leverage, liquidity (current ratio) and asset efficiency (total asset turnover) and the dependent variable is the sustainable growth rate (SGR) of the company. The data of the research consists of 162 companies selected on the criterion of medium taxpayers from real estate and construction sector of the North-West region of Romania. The comparison between the financial data of the companies before and during the pandemic shows an increase in net profit and dividends and the empirical results shows that financial leverage and liquidity have a negative impact effect on company’s sustainable growth, while asset efficiency has a positive impact. The results and findings of the study have their limitations, which consist in modelling of reduced number of variables, the existence of other factors that could influence the results.
Keywords: sustainable grow rate; leverage; liquidity; asset efficiency; constructions; real estate